Energy and Seismic Retrofit of Historic Buildings in New Zealand: Reflections on Current Policies and Practice. (2nd January 2020) - Besen, Priscila; Boarin, Paola; Haarhoff, Errol
ABSTRACT: Built heritage plays an important role in making history visible in New Zealand's cities. However, ensuring that historic heritage can withstand future challenges such as climate change and seismic resilience is key to ensure its preservation, as the country has had countless examples of lost heritage due to earthquakes, fire, lack of maintenance and decay resulting from inadequate indoor environmental conditions. New regulations came into force in 2017 for earthquake-prone buildings, which set up timeframes for all buildings to achieve minimum structural standards. As a result, there are many seismic strengthening projects taking place, especially for Unreinforced Masonry (URM) buildings, identified as one of the most vulnerable construction types. However, the other future challenge for historic buildings will be to deal with climate change – ensuring buildings can withstand extreme conditions while maintaining comfortable indoor conditions, without demanding excessive energy input. So far, energy considerations have not been extensively included as parameters in retrofit projects, in existing policies or in practice. This contribution analyses current policies and practice for retrofitting historic buildings in New Zealand, aiming to understand the current barriers, challenges and possibilities for energy retrofitting historic buildings in the country as a combined strategy with seismic upgrading.